2022
DOI: 10.1029/2021gl096171
|View full text |Cite
|
Sign up to set email alerts
|

Springtime Stratospheric Volcanic Aerosol Impact on Midlatitude Cirrus Clouds

Abstract: Explosive volcanic eruptions can reach the stratosphere and cause elevated concentrations of sulphate particles for months to years. When these particles descend into the troposphere, they can impact cirrus clouds though to what degree is unknown. In this study, we combine three satellite data sets to investigate the impact of downwelling sulphate aerosol on midlatitude cirrus clouds during springtime. The results show that cirrus clouds in the northern hemisphere (NH) have lower ice water content (IWC), ice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…They modify the global radiative budget by scattering and absorbing solar shortwave and terrestrial longwave radiation. Aerosols in the lower stratosphere also affect the cloud life cycle by acting as ice nuclei (Sporre et al, 2022). Studies have shown that approximately 21% of the overall direct aerosol radiative forcing since 1850 can be attributed to stratospheric aerosols (Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They modify the global radiative budget by scattering and absorbing solar shortwave and terrestrial longwave radiation. Aerosols in the lower stratosphere also affect the cloud life cycle by acting as ice nuclei (Sporre et al, 2022). Studies have shown that approximately 21% of the overall direct aerosol radiative forcing since 1850 can be attributed to stratospheric aerosols (Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%